Pengelolaan Bimbingan Sosial Siswa Kelas XII IPA SMA Negeri 1 Sukodono Sragen - Susena, Muhammad Agus; , Prof. Dr. Bambang Sumarjoko; , Drs. Budi Sutrisno, M. Pd (2015)
Muhammad Agus Susena. Q. 100 120 32. The Social Guidance Management of 12 th Grade Students of Science Studies at SMA Negeri 1 Sukodono Sragen. Tesis. Program Studi Manajemen Pendidikan Program Pascasarjana Universitas Muhammadiyah Surakarta. 2015. The objectives of the research are to describe: 1) the social gudance planning; 2) the implementation of social guidance; and 3) the feedback of social guidance management for the 12 th grade students of Science Studies at SMA Negeri 1 Sukodono Sragen. The type of the research is a qualitative research. The design of the researh is ethnographical design. The research was undertaken at SMA Negeri 1 Sukodono Sragen. The object of the research was the implementation of social guidance provided to the 12 th grade students of Science Studies. The subjects of the research are the principal, guidance and counseling teachers, and students engaged in the social guidance process. The data collecting method is done using observation, in-depth interview, and document techniques. The data analysis is done using interactive model consists of three main components, namely data reduction, data display, and verification. The data validation is done using continuous observation, data triangulation, and member check techniques. The research concludes that: 1) the social guidance planning is done through: a) the mapping of needs, problems, and context; and b) the design of program that fit to the needs, problems, and the context; 2) the implementation of social guidance were done through the settlement of school's code of conduct, the guidance and conseling implementation undertaken by the Guidance and Counseling teachers, and the educative sanction provided to the students that violate the school's code of conduct.; and 3) the social gudance feedback is undertaken at the end of the semester. The prgram evaluation results are in the form of description on evaluated aspects. The describe the extent of the social guidance support the students' improvement.